Analysis of the HBsAg status of toddlers born to HbsAg-reactive mothers at the Sikumana Community Health Center, Kupang City, in 2021 - Rosina Kardina Kidi Hurek; Theresia Mindarsih; Frida Sisternike Pay (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background: Hepatitis is an infectious disease which is regarded as a public health problem due to its high prevalence. It is an inflammation of the liver that may develop into fibrosis, cirrhosis or liver cancer. The data obtained from the basic health research in 2017 shows that East Nusa Tenggara has the second highest percentage of HBsAg reactive-amongpregnant women in Indonesia (5.26%). Objectives: This study aims to analyze the HBsAg status of toddlers born from pregnant women with HbsAg-reactive at the Sikumana Health Center, Kupang City, in 2021. Methods: This is an analytical research carried out with a quantitative approach carried out and a cross sectional research design. This research was conducted at the Sikumana Community Health Center in September-October 2021 with a total sample of 53 toddlers born to HBsAg-reactive pregnant women in 2019. The data used were primary data collected using instruments in the form of questionnaires and blood samples taken for the HBsAg examination which was carried out by laboratory workers at the Sikumana Community Health Center. Meanwhile, the data analysis was performed using univariate and bivariate (chi square) method with version 20 of SPSS application.Results: The results show that there were 53 HbsAg-reactive pregnant women at the Sikumana Community Health Center, Kupang City, and most of whom (83.0%) had good knowledge about Hepatitis B. The HBsAg RDT test in infants born to pregnant women with HbsAg-reactive revealed that there were 4 toddlers (7.5%) with HBsAg reactive, indicating that there was still a failure in immunoglobulin (HBIg). Furthermore, the results of the chi square test showed that there was a relationship between mother's knowledge, child's age, and history of HBIG administration with toddler's HBsAg status.Conclusions: Health workers are expected to increase education and socialization about Hepatitis B and the importance of re-examination of infants who have received HBIG immunoprophylaxis. The re-examination is necessary considering that the confirmation examination program for the HBsAg RDT test has not been going well and immunoglobulin (HBIg) failures still occurred even if only in small number. Furthermore, this re-examination plays pivotal role to detect the effectiveness of HBIG so that early treatment can be given if there is a HBIG failure.